Employee silence in health care: Charting new avenues for leadership and management. Issue 1 (16th January 2023) - Montgomery, Anthony; Lainidi, Olga; Johnson, Judith; Creese, Jennifer; Baathe, Fredrik; Baban, Adriana; Bhattacharjee, Anindo; Carter, Madeline; Dellve, Lotta; Doherty, Eva; Jendeby, Mimmi Kheddache; Morgan, Karen; et al.
Abstract : Issue: Health care management is faced with a basic conundrum about organizational behavior; why do professionals who are highly dedicated to their work choose to remain silent on critical issues that they recognize as being professionally and organizationally significant? Speaking-up interventions in health care achieve disappointing outcomes because of a professional and organizational culture that is not supportive. Critical Theoretical Analysis: Our understanding of the different types of employee silence is in its infancy, and more ethnographic and qualitative work is needed to reveal the complex nature of silence in health care. We use the sensemaking theory to elucidate how the difficulties to overcoming silence in health care are interwoven in health care culture. Insight/Advance: The relationship between withholding information and patient safety is complex, highlighting the need for differentiated conceptualizations of silence in health care. We present three Critical Challenge points to advance our understanding of silence and its roots by (1) challenging the predominance of psychological safety, (2) explaining how we operationalize sensemaking, and (3) transforming the role of clinical leaders as sensemakers who can recognize and reshape employee silence. These challenges also point to how employee silence can also result in a form of dysfunctional professionalism that supports maladaptive health care structures in practice. Practice Implications: Delineating the contextual factors that prompt employee silence and encourage speaking up among health care workers is crucial to addressing this issue in health care organizations. For clinical leaders, the challenge is to valorize behaviors that enhance adaptive and deep psychological safety among teams and within professions while modeling the sharing of information that leads to improvements in patient safety and quality of care.